Developing career pathways and work flexibility to enhance employee spirit: A case study of the Lost and Found Department at PTJAS company - Waelan, Waelan; Kusminantari, Anik; Nadra, Nyoman Mastiani; Sarjana, I Made (Yayasan Mitra Persada Nusantara, 2024)
The aim of this study is to develop a comprehensive model for career path development and work flexibility to enhance employee morale in the Lost and Found Department of PTJAS company. This research addresses the growing need for adaptable career structures and flexible work arrangements as pivotal factors in improving job satisfaction and employee engagement. Data were collected using a mixed-methods approach, comprising surveys and interviews with employees in the Lost and Found Department. The survey data provided quantitative insights into employee satisfaction levels, while the interviews offered qualitative perspectives on the impact of career paths and work flexibility on morale. The analysis revealed a strong correlation between clearly defined career paths, flexible work options, and heightened employee morale. Employees who perceived clear advancement opportunities and enjoyed flexible working conditions reported significantly higher job satisfaction and motivation levels. Additionally, the findings suggest that implementing these strategies can lead to reduced turnover rates and improved organizational commitment. In conclusion, the study underscores the importance of integrating career development and work flexibility into the organizational framework to foster a positive work environment. These insights are crucial for HR professionals and management of the company aiming to boost employee morale and productivity.